“Noi vi havemo consumato in questa pratica la vita et l’intelletto nostro”: un parere inedito di Pio V (1556) (Stato, Chiese e pluralismo confessionale, 2021)
SOMMARIO: 1. “La vita et l’intelletto nostro”: un inedito vaticano - 2. “In questa pratica”: il fascicolo manoscritto - 2.1. Il Barberiniano Latino 1369: struttura e datazione dei sette responsi - 2.2. La questione avanti il Sant’Uffizio: i confini dell’autorità inquisitoriale - 2.2.1. I cinque pareri pro - 2.2.2. I due pareri contra - 3. “Noi vi havemo consumato”: la quaestio del Ghislieri - 3.1. Propositio - 3.2. Oppositio - 3.3. Solutio - 4. Conclusioni - Appendice.“Noi vi havemo consumato in questa pratica la vita et l’intelletto nostro”: an unpublished opinion by Pius V (1556)ABSTRACT: Long before being enthroned as Pope with the name of Pius V (1566), Michele Ghislieri worked tirelessy and enthusiastically for the Roman Inquisition under Paul IV and his successors, building and cementing his position within the Roman Curia. In his capacity as commissary of the Holy Office (1556), Ghislieri was requested to express an opinion regarding the relationship of inquisitorial and episcopal jurisdictions in receiving abjurations. This opinion, delivered in the form of a quaestio of the medieval scolastic tradition and published here for the first time, casts new light not only on the intellectual biography of this famous Pope but also, given the fact that he was not the only consultor whose opinion was requested, on the daily work of the Roman tribunal and, in more general terms, on the capital importance of law within the spectrum of Western cultural system in Early Modern age.